ANALISIS KEBIJAKAN DIVIDEN : Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Erika Hadi Septiani (2021)
This Research is using quantitative study aimed to see whether there are influence of profitability, liquidity, leverage, inflation, and bi rate on dividend policy. This study uses manufacturing companies listed on the Indonesian Stock Exchange as samples. This study uses non-probability sampling with purposive sampling as sampling method. Testing the hypothesis in this study was used Data Panel Regression Analisys using Eviews 11.0 tool with a significant level of 0.05 %. The results of these tests indicate that (1)there is positive significant influence of profitability on dividend policy, (2)there is negative significant influence of leverage on dividend policy and (3)there is no significant effect liquidity, inflation and BI Rate on dividend policy.